Effect of Depth of Sowing on Germination of Spruce (Picea Smythiana) Seeds - Singh, R. V.; Chandra, J. P.; Sharma, R. K. (Indian Forester, 1975)
The results of two experiments conducted to study the effect of the depth of sowing on germination of spruce seeds are summarised. In both these experiments the germination percentage decreased as the depth of sowing increased; the decrease being very much marked with sowings done at a depth of 15 mm and more. Deeper sowings delayed germination and the number of days taken for the commencement of germination increased with an increase in the depth of sowing. The results of these experiments show that spruce should be sown as shallow as possible and in no case deeper than to 10 mm.